Resistensi dalam Psikoterapi Terhadap Trauma KDRT Pada Anak (Perspektif Psikoanalisa) - Evita Yuliatul Wahidah (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2017)
Abstract: Psychological resistance is a phenomenon that is often encountered in clinical practice where the patient either directly or indirectly change their behavior oppose or refuse to discuss, remember, or think about the experience may be clinically relevant. Resistance could impinge on child trauma of domestic violence. And it is important to understand that domestic violence exposure in children can cause various problems in both the short and long term. In the short term such as: threats to the safety of life of children, damaging the structure of the family, the emergence of various mental disorders; whereas in the long term raises the potential of children engaged in violent behavior and abuse in the future, either as perpetrators or victims. Psychoanalytic theory gives a resolution deals Trauma Psychotherapy Against Domestic Violence on Children In include: Free Association, Interpretation (Interpretation), and the analysis of dreams. For this paper to begin discussion of the notion of resistance, understanding and concepts of psychotherapy for the child trauma of domestic violence within the perspective of psychoanalysis.Keywords: Resistensi, Psikoterapi, Trauma KDRT, Psikoanalisa.